Given fmap id = id, fmap (f . g) = fmap f . fmap g follows from the free theorem for fmap.
 
This was published as an aside in a paper a long time back, but I forget where.
-Edward Kmett
 
On Mon, Jan 4, 2010 at 5:14 PM, Paul Brauner <paul.brauner@loria.fr> wrote:
Hi,

I'm trying to get a deep feeling of Functors (and then pointed Functors,
Applicative Functors, etc.). To this end, I try to find lawless
instances of Functor that satisfy one law but not the other.

I've found one instance that satisfies fmap (f.g) = fmap f . fmap g
but not fmap id = id:

data Foo a = A | B

instance Functor Foo where
 fmap f A = B
 fmap f B = B

-- violates law 1
fmap id A = B

-- respects law 2
fmap (f . g) A = (fmap f . fmap g) A = B
fmap (f . g) B = (fmap f . fmap g) B = B

But I can't come up with an example that satifies law 1 and not law 2.
I'm beginning to think this isn't possible but I didn't read anything
saying so, neither do I manage to prove it.

I'm sure someone knows :)

Paul
_______________________________________________
Haskell-Cafe mailing list
Haskell-Cafe@haskell.org
http://www.haskell.org/mailman/listinfo/haskell-cafe